An approximate solution of the spherical indentation on a generally anisotropic elastic half-space. (April 2019) - Zhou, Lei; Wang, Shibin; Li, Linan; Wei, Huixin; Dai, Anna
Highlights: An approximate solution of spherical indentation on elastically anisotropic half space is given, where the exact geometrical relation on the edge of contact and its approximate form are both considered. A specific tensor of instantaneous elastic moduli is given to characterize the mechanical property of fiber-reinforced material. The specific solution of spherical indentation by applying the above material model presents an approach to determine the material parameters of fiber-reinforced material by indentation test. The numerical results based on FEM validate the associated work. Abstract: The indentation of a generally anisotropic elastic half-space by a rigid spherical indentor is considered. We derive an approximate equation for the eccentricity of the ellipsoidal contact region and an approximate expression for the indentation modulus. Our approximate formulae are first validated by ABAQUS-based numerical simulations, and then specialized to the particular case of a fibre-reinforced composite half-space. Numerical results are presented to show the dependence of the eccentricity and indentation modulus on the compressibility and fibre strength of the composite material. Possible application of our approximate formulae to the determination of elastic constants of fibre-reinforced materials is discussed.